Dramatic language semiotics (Journal of the College of Basic Education, 2023)
Critical studies have produced many cognitive terms and concepts that dealt withThe embodiment of the creative text, and perhaps one of the concepts produced by these studies is the term(Sima), which created a cognitive debate in the fields of reading and criticism of the body of the text and its decoding.He changed many concepts towards him, who was subject to the reading of the same author's ranges, inWhen the face sees the text standing on its own, possessing the elements of its creativity that the recipient draws by deconstructingIts code is a function and its focus with its different meanings from outside the text through the relational construction of the elementstext.